Mediating Role Of Satisfaction And Moderating Role Of Perceived Value: A Empirical Study Of Electronic Commerce In Indonesia - M. Munir Syam AR; Edy Purwanto; Miftahol Arifin (UNIVED Press, 2024)
This research develops a research model where satisfaction is a mediating variable in the influence of e-service quality on loyalty. Then, perceived value acts as a moderating variable of the influence of satisfaction on loyalty. The object of this research is electronic commerce (e-commerce) in Indonesia. The sample in this study was 260 respondents taken using a purposive sampling technique. The respondent criteria used are that the respondent has an account at an online shop such as Shopee, Lazada, Tokopedia, and other online shops. Respondent also has made purchases at these online shops. Data was obtained through distributing questionnaires. Hypothesis testing is carried out using simple regression analysis, mediation tests, and moderation tests using the Hierarchical Moderated Regression (HRM) technique. Research finds that partially e-service quality has a significant influence on Satisfaction and also on Loyalty. Satisfaction also has a significant influence on loyalty. This research also found that satisfaction is a variable that can mediate the influence of E-service quality on loyalty. However, on the contrary, this research found that perceived value does not moderate the influence of satisfaction on the loyalty of E-Commerce users.